A kind of preparation method of cobalt green pigment

By using hydrothermal reaction and ball milling calcining methods of cobalt, zinc, chromium and neodymium oxide, the problems of high energy consumption and complex process in the existing cobalt green pigment preparation methods are solved, and cobalt green with excellent comprehensive performance is prepared. Pigments are suitable for industrial production.

CN118993162BActive Publication Date: 2025-02-07HUNAN HUIBANG ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411483592.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-07
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing cobalt green pigment preparation methods have problems such as high energy consumption, complex process, uneven pigment particle size, and dark color, which are difficult to meet the needs of industrial production.

Method used

Cobalt green pigments with small average particle size, bright color and good stability are prepared by using cobalt source, zinc source, chromium source and neodymium oxide as raw materials.

Benefits of technology

It realizes low energy consumption and high efficiency preparation of cobalt green pigments. The pigments have excellent heat resistance, solvent resistance, weather resistance and dispersion, and are suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of pigments, and discloses a method for preparing a cobalt green pigment, comprising the following steps: (1) adding a cobalt source, a zinc source, a chromium source and neodymium oxide into water, stirring and mixing to obtain a mixed metal solution, then adding polyethylene glycol and ethylene glycol amine, stirring and mixing, and adjusting the pH to alkaline to obtain a mixed solution; (2) transferring the mixed solution obtained in step (1) into a closed reactor, performing a hydrothermal reaction, cooling, filtering, washing the filter residue with water, and freeze-drying to obtain a cobalt green pigment precursor; (3) subjecting the cobalt green pigment precursor obtained in step (2) to ball milling treatment, calcining under a protective atmosphere, and cooling to obtain a cobalt green pigment. The cobalt green pigment obtained by the method of the invention has a small average particle size, good heat resistance, solvent resistance, and weather resistance, good dispersibility and tinting strength, bright and lasting color, good stability, low energy consumption, simple process, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pigments, and in particular to a method for preparing a cobalt green pigment. Background Art

[0002] Cobalt green is an important ceramic pigment with a spinel structure. It has a unique yellow-green color and bright tones. It is widely used in high-temperature resistant coatings, plastics, ceramics, enamels, glass and other fields. It is non-toxic and environmentally friendly, and has excellent weather resistance, acid and alkali resistance and high infrared reflectivity. It performs particularly well in fields that require ultra-durability. It has high color retention, gloss retention and anti-powdering properties, and is superior to other green pigments in terms of chroma and saturation.

[0003] Most traditional cobalt green pigment preparation methods use a dry method, that is, a solid-phase method, in which the raw materials are mixed and then directly subjected to solid-phase high-temperature calcination. This method has high calcination temperature and high energy consumption, and the reaction rate is affected by diffusion dynamics. The obtained pigment particle size is large and uneven, and the color is dark, and there are great defects in application performance. The sol-gel method uses metal organic or inorganic compounds as raw materials to prepare a solution, and then undergoes hydrolysis and polycondensation reaction, and then is dried and calcined to obtain a green pigment. The cost of the raw materials is high, the preparation cycle is long, and the post-processing is difficult.

[0004] Therefore, it is particularly important to develop a method with low energy consumption, simple process and the ability to prepare high-quality cobalt green pigment. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the above-mentioned defects of the prior art and provide a method for preparing a cobalt green pigment having a small average particle size, good heat resistance, solvent resistance, and weather resistance, good dispersibility and tinting power, bright and lasting color, good stability, low energy consumption, simple process, and suitable for industrial production.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: a method for preparing a cobalt green pigment comprises the following steps:

[0007] (1) adding a cobalt source, a zinc source, a chromium source and neodymium oxide into water, stirring and mixing to obtain a mixed metal solution, then adding polyethylene glycol and ethylene glycol amine, stirring and mixing, and adjusting the pH to alkaline to obtain a mixed solution;

[0008] (2) transferring the mixed solution obtained in step (1) into a closed reactor, performing a hydrothermal reaction, cooling, filtering, washing the filter residue with water, and freeze-drying to obtain a cobalt green pigment precursor;

[0009] (3) The cobalt green pigment precursor obtained in step (2) is ball-milled, calcined and cooled under a protective atmosphere to obtain a cobalt green pigment.

[0010] The inventive idea of ​​the method of the present invention is: the method of the present invention uses a cobalt source, a zinc source, and a chromium source as raw materials, and then uses neodymium oxide as a dopant, through a hydrothermal reaction, and then undergoes ball milling and calcination treatment to prepare a cobalt green pigment precursor. Raw materials such as cobalt sources, zinc sources, and chromium sources are relatively abundant in nature. Compared with the single use of scarce cobalt resources, the acquisition cost of these raw materials is lower. Using multiple metals as raw materials can not only reduce the preparation cost, but also enable the cobalt-containing green pigment obtained by the method of the present invention to form a composite spinel structure, and can also make the appearance of the obtained pigment appear bright green.

[0011] Preferably, in step (1), the molar ratio of the cobalt element in the cobalt source, the zinc element in the zinc source, the chromium element in the chromium source and the metal element in the neodymium oxide is 1:0.14-0.32:1.1-1.8:0.08-0.16. Neodymium oxide has good optical and electrical properties. After addition, it can improve the color brightness, color fastness and optical properties of the cobalt green pigment, so that it can show better visual effects and durability in various applications. It can also enhance the weather resistance of the pigment, so that it can maintain stable color performance under different climatic conditions.

[0012] Preferably, in step (1), the mass ratio of the cobalt source to water is 1:15-18.

[0013] Preferably, in step (1), the mass ratio of the mixed metal solution to polyethylene glycol and ethylene glycol amine is 100:5-9:2-3.

[0014] In the process of preparing the cobalt green pigment precursor by hydrothermal reaction, adding polyethylene glycol can not only promote the dispersion of the mixed solution, but also affect the growth process of the crystal as a morphology regulator by adsorbing on the specific crystal plane of the crystal, controlling the morphology and size of the product, and can also stabilize the reaction system, prevent the agglomeration and precipitation of nanoparticles, and ensure the smooth progress of the reaction. Ethylene glycol amine has a certain complexing ability and forms a complex with metal ions, thereby reducing the hydrolysis rate of metal ions and improving the stability of the reaction system. Its surface activity can also reduce the surface tension of the reaction system. In particular, ethylene glycol amine helps to stabilize cobalt ions and prevent premature hydrolysis to form cobalt hydroxide precipitation.

[0015] Preferably, in step (1), the cobalt source includes one or more of cobalt sulfate, cobalt chloride or cobalt nitrate and hydrates thereof.

[0016] Preferably, in step (1), the zinc source includes one or more of zinc sulfate, zinc chloride or zinc nitrate and hydrates thereof.

[0017] Preferably, in step (1), the chromium source includes one or more of chromium trichloride, chromium sulfate or chromium nitrate and hydrates thereof.

[0018] Preferably, in step (1), the stirring and mixing temperature is room temperature, the stirring speed is 500-600 r / min, and the time is 30-60 min.

[0019] Preferably, in step (1), the pH is adjusted to 8-10 using an alkaline solution having a concentration of 1-3 mol / L. By adjusting the reaction system to alkalinity, the reactants are coprecipitated to generate a cobalt green pigment precursor.

[0020] Preferably, in step (1), the base is sodium hydroxide and / or potassium hydroxide.

[0021] Preferably, in step (2), the temperature of the hydrothermal reaction is 150-210° C., the pressure is 2-4 MPa, and the time is 6-12 h.

[0022] Preferably, in step (2), the freeze-drying temperature is -50 to -90°C, the pressure is 0.01 to 0.10 MPa, and the freeze-drying time is 36 to 60 hours.

[0023] Preferably, in step (3), the rotation speed of the ball milling treatment is 1200-1500 r / min, and the time of the ball milling treatment is 18-25 min.

[0024] The method of the invention processes the cobalt green pigment precursor by ball milling, breaks it into smaller particles, and makes its distribution more uniform, which can not only improve the dispersibility of the pigment, but also increase the specific surface area of ​​the pigment, and improve its tinting power and hiding power.

[0025] Preferably, in step (3), the protective atmosphere is one or more of nitrogen, argon or helium, etc. The protective atmosphere used in the method of the present invention is a high-purity atmosphere with a purity of ≥99.9%.

[0026] Preferably, in step (3), the calcination is carried out by heating the mixture to 900-1050° C. at a rate of 2-5° C. / min and calcining for 1-3 h.

[0027] The method of the present invention can remove impurities in the cobalt green pigment precursor after ball milling by calcining the precursor, making the chemical composition more uniform, and can also optimize the crystal structure in the precursor, thereby improving its crystallinity and stability.

[0028] The beneficial effects of the method of the present invention are as follows:

[0029] (1) The present invention provides a method for preparing a cobalt green pigment having small average particle size, good heat resistance, solvent resistance, weather resistance, good dispersibility and tinting power, bright and lasting color, good stability, low energy consumption, simple process, and suitable for industrial production; a cobalt green pigment precursor is prepared by using a cobalt source, a zinc source, and a chromium source as raw materials, and then using neodymium oxide as a dopant, through a hydrothermal reaction, and then through ball milling and calcination treatment; the raw materials such as the cobalt source, the zinc source, and the chromium source are relatively abundant in nature, and the acquisition cost of these raw materials is lower than that of the single use of scarce cobalt resources; using multiple metals as raw materials can not only reduce the preparation cost, but also enable the cobalt-containing green pigment obtained by the method of the present invention to form a composite spinel structure, and also enable the appearance of the obtained pigment to be bright green; the neodymium oxide used has good optical and electrical properties, and after being added, it can improve the color brightness, color fastness and optical properties of the cobalt green pigment, so that it can show better visual effects and durability in various applications, and can also enhance the weather resistance of the pigment, so that it can maintain stable color performance under different climatic conditions;

[0030] (2) In the process of preparing the cobalt green pigment precursor by hydrothermal reaction, the addition of polyethylene glycol can not only promote the dispersion of the mixed solution, but also act as a morphology regulator. By adsorbing on the specific crystal plane of the crystal, it affects the growth process of the crystal, controls the morphology and size of the product, stabilizes the reaction system, prevents the aggregation and precipitation of nanoparticles, and ensures the smooth progress of the reaction. Ethylene glycol amine has a certain complexing ability and forms a complex with metal ions, thereby reducing the hydrolysis rate of metal ions and improving the stability of the reaction system. Its surface activity can also reduce the surface tension of the reaction system. In particular, ethylene glycol amine helps to stabilize cobalt ions and prevent premature hydrolysis to form cobalt hydroxide precipitates.

[0031] (3) The present invention processes the cobalt green pigment precursor by ball milling to break it into smaller particles, which can make its distribution more uniform, not only improving the dispersibility of the pigment, but also increasing the specific surface area of ​​the pigment, improving its tinting power and hiding power; calcining the precursor can remove impurities in the cobalt green pigment precursor after ball milling, making the chemical composition more uniform, and can also optimize the crystal structure in the precursor, improving its crystallinity and stability;

[0032] (4) The cobalt green pigment obtained by the method of the present invention has a small average particle size and excellent comprehensive properties. The heat resistance temperature is as high as 1209°C, the heat resistance is good, the solvent resistance is excellent, and the weather resistance is as high as level 5, which means that the color fastness is high, the color is bright and lasting, the stability is good, the dispersibility is good, and there is no flocculation during dispersion, which greatly reduces the calcination temperature and insulation time of the product preparation, and there is no need to post-treat the calcined cobalt green pigment, the energy consumption is low, the process is simple, and it is suitable for industrial production. DETAILED DESCRIPTION

[0033] The present invention will be further described below in conjunction with the embodiments.

[0034] The protective atmosphere used in the examples and comparative examples of the present invention is a high-purity atmosphere with a purity of ≥99.9%; the raw materials or chemical reagents used in the examples and comparative examples of the present invention, unless otherwise specified, are obtained through conventional commercial channels.

[0035] Example 1

[0036] (1) 10 g (64.5 mmol) of cobalt sulfate, 1.5 g (9.3 mmol) of zinc sulfate, 12 g (75.8 mmol) of chromium trichloride, and 0.9 g (2.7 mmol) of neodymium oxide were added to 150 g of deionized water, and stirred at room temperature and a stirring speed of 500 r / min for 30 min to obtain a mixed metal solution, and then 8.72 g of polyethylene glycol and 3.49 g of ethylene glycolamine were added, and stirred at room temperature and a stirring speed of 500 r / min for 60 min, and the pH value was adjusted to 8 with a 2 mol / L sodium hydroxide solution to obtain a mixed solution;

[0037] (2) transferring the mixed solution obtained in step (1) into a sealed polytetrafluoroethylene reactor, performing a hydrothermal reaction at 150° C. and 2 MPa for 6 h, cooling, filtering, washing the filter residue with deionized water, and freeze-drying at -50° C. and 0.01 MPa for 48 h to obtain a cobalt green pigment precursor;

[0038] (3) The cobalt green pigment precursor obtained in step (2) is placed in a ball mill and subjected to ball milling treatment at a rotation speed of 1200 r / min for 18 min. The ball mill is then transferred to a tubular furnace and heated to 900° C. at a rate of 2° C. / min in a high-purity helium atmosphere. The product is calcined for 3 h and then cooled to room temperature in the furnace to obtain a cobalt green pigment.

[0039] Example 2

[0040] (1) 10 g (64.5 mmol) of cobalt sulfate, 2.1 g (13.0 mmol) of zinc sulfate, 15 g (94.7 mmol) of chromium trichloride, and 1.2 g (3.6 mmol) of neodymium oxide were added to 160 g of deionized water, and stirred at room temperature and a stirring speed of 550 r / min for 45 min to obtain a mixed metal solution, and then 13.18 g of polyethylene glycol and 4.52 g of ethylene glycolamine were added, and stirred at room temperature and a stirring speed of 550 r / min for 45 min, and the pH value was adjusted to 9 with a 2 mol / L sodium hydroxide solution to obtain a mixed solution;

[0041] (2) transferring the mixed solution obtained in step (1) into a sealed polytetrafluoroethylene reactor, performing a hydrothermal reaction at 180° C. and 2.5 MPa for 9 h, cooling, filtering, washing the filter residue with deionized water, and freeze-drying at -70° C. and 0.05 MPa for 48 h to obtain a cobalt green pigment precursor;

[0042] (3) The cobalt green pigment precursor obtained in step (2) is placed in a ball mill and subjected to ball milling treatment at a rotation speed of 1400 r / min for 21 min. The ball mill is then transferred to a tubular furnace and heated to 950° C. at a rate of 3° C. / min in a high-purity helium atmosphere. The mixture is calcined for 2 h and then cooled to room temperature to obtain a cobalt green pigment.

[0043] Example 3

[0044] (1) 10 g (64.5 mmol) of cobalt sulfate, 2.8 g (17.3 mmol) of zinc sulfate, 16.5 g (104.2 mmol) of chromium trichloride, and 1.4 g (4.2 mmol) of neodymium oxide were added to 170 g of deionized water, and stirred at room temperature and a stirring speed of 550 r / min for 45 min to obtain a mixed metal solution, and then 16.06 g of polyethylene glycol and 5.62 g of ethylene glycolamine were added, and stirred at room temperature and a stirring speed of 550 r / min for 45 min, and the pH value was adjusted to 9 with a 2 mol / L sodium hydroxide solution to obtain a mixed solution;

[0045] (2) transferring the mixed solution obtained in step (1) into a sealed polytetrafluoroethylene reactor, performing a hydrothermal reaction at 200° C. and 3.5 MPa for 10 h, cooling, filtering, washing the filter residue with deionized water, and freeze-drying at -70° C. and 0.05 MPa for 48 h to obtain a cobalt green pigment precursor;

[0046] (3) The cobalt green pigment precursor obtained in step (2) is placed in a ball mill and subjected to ball milling treatment at a rotation speed of 1450 r / min for 24 min. The ball mill is then transferred to a tubular furnace and heated to 1000° C. at a rate of 3° C. / min in a high-purity helium atmosphere. The product is calcined for 2.5 h and then cooled to room temperature in the furnace to obtain a cobalt green pigment.

[0047] Example 4

[0048] (1) 10 g (64.5 mmol) of cobalt sulfate, 3.2 g (19.8 mmol) of zinc sulfate, 18 g (113.7 mmol) of chromium trichloride, and 1.6 g (4.8 mmol) of neodymium oxide were added to 180 g of deionized water, and stirred at room temperature and a stirring speed of 600 r / min for 60 min to obtain a mixed metal solution, and then 19.15 g of polyethylene glycol and 6.38 g of ethylene glycolamine were added, and stirred at room temperature and a stirring speed of 600 r / min for 60 min, and the pH value was adjusted to 10 with a 2 mol / L sodium hydroxide solution to obtain a mixed solution;

[0049] (2) transferring the mixed solution obtained in step (1) into a sealed polytetrafluoroethylene reactor, performing a hydrothermal reaction at 210° C. and 4 MPa for 12 h, cooling, filtering, washing the filter residue with deionized water, and freeze-drying at -90° C. and 0.07 MPa for 48 h to obtain a cobalt green pigment precursor;

[0050] (3) The cobalt green pigment precursor obtained in step (2) is placed in a ball mill and subjected to ball milling treatment at a rotation speed of 1500 r / min for 25 min. The ball mill is then transferred to a tubular furnace and heated to 1050° C. at a rate of 5° C. / min in a high-purity helium atmosphere. The mixture is calcined for 1 h and then cooled to room temperature in the furnace to obtain a cobalt green pigment.

[0051] Comparative Example 1

[0052] The difference between this comparative example and Example 3 is that in step (1), no neodymium oxide is added. The rest is the same as Example 3.

[0053] Comparative Example 2

[0054] The difference between this comparative example and Example 3 is that in step (3), ball milling is not performed. The rest is the same as Example 3.

[0055] In order to evaluate the difference in particle size distribution of the cobalt green pigment obtained in Examples 1 to 4 of the present invention and Comparative Examples 1 and 2, a particle size test was performed using an SKC-2000 light transmission particle size distribution tester. The test results are shown in Table 1.

[0056] Table 1 Comparison of the particle sizes of the cobalt green pigments obtained in Examples 1 to 4 of the present invention and Comparative Examples 1 and 2

[0057]

[0058] Note: In the table, the particle size ranges of 0.01-0.10μm, 0.10-0.50μm, and 0.50-1.00μm do not include the lower limits of 0.01μm, 0.10μm, and 0.50μm, respectively.

[0059] As shown in Table 1, the cobalt green pigments obtained in Examples 1 to 4 of the present invention have a smaller average particle size and less large particle size distribution than those obtained in Comparative Examples 1 and 2. Among them, the cobalt green pigment obtained in Example 3 of the present invention has the smallest average particle size. No neodymium oxide was added in Comparative Example 1, which had little effect on the particle size of the cobalt green pigment; no ball milling was performed in Comparative Example 2, and the particle size distribution was large, and 65.32% of the cobalt green pigments had a particle size greater than 1.00 μm.

[0060] In order to evaluate the comprehensive performance of the cobalt green pigment obtained in Examples 1 to 4 of the method of the present invention and Comparative Examples 1 and 2, the heat resistance, solvent resistance, weather resistance and dispersibility were tested respectively. The test standard of heat resistance refers to HG / T 3853-2006, the test standard of solvent resistance refers to GB / T 5211.9-85, and the test standard of weather resistance refers to GB / T 250-2008. The test method of dispersibility is to mix the cobalt green pigment with an appropriate amount of water, grind it in a grinder, and observe the flocculation of the pigment particles after grinding. The test results are shown in Table 2.

[0061] Table 2 Comprehensive performance comparison of cobalt green pigments obtained in Examples 1 to 4 of the present invention and Comparative Examples 1 and 2

[0062]

[0063] As shown in Table 2, the cobalt green pigment obtained in Examples 1 to 4 of the present invention has excellent comprehensive performance, and its weather resistance reaches level 5, indicating that it has high color fastness, bright and lasting color, and good stability; excellent solvent resistance, good dispersibility, and no flocculation during dispersion; among them, the heat resistance of the cobalt green pigment obtained in Example 3 of the present invention reaches 1209°C. The weather resistance of Comparative Examples 1 and 2 is relatively low, and the dispersibility of the cobalt green pigment obtained in Comparative Example 2 is poor, and there is a partial flocculation phenomenon.

Claims

1. A method for preparing a cobalt green pigment, characterized in that: The following steps are involved: (1) adding a cobalt source, a zinc source, a chromium source and neodymium oxide into water, stirring and mixing to obtain a mixed metal solution, then adding polyethylene glycol and ethylene glycol amine, stirring and mixing, and adjusting the pH to alkaline to obtain a mixed solution; (2) transferring the mixed solution obtained in step (1) into a closed reactor, performing a hydrothermal reaction, cooling, filtering, washing the filter residue with water, and freeze-drying to obtain a cobalt green pigment precursor; (3) ball-milling the cobalt green pigment precursor obtained in step (2), calcining under a protective atmosphere, and cooling to obtain a cobalt green pigment; In step (1), the molar ratio of the cobalt element in the cobalt source, the zinc element in the zinc source, the chromium element in the chromium source and the metal element in the neodymium oxide is 1:0.14-0.32:1.1-1.8:0.08-0.16; the mass ratio of the cobalt source to water is 1:15-18; the mass ratio of the mixed metal solution to polyethylene glycol and ethylene glycol amine is 100:5-9:2-3; In step (2), the temperature of the hydrothermal reaction is 150 to 210°C, the pressure is 2 to 4 MPa, and the time is 6 to 12 hours; the temperature of the freeze-drying is -50 to -90°C, the pressure is 0.01 to 0.10 MPa, and the time of the freeze-drying is 36 to 60 hours; In step (3), the rotation speed of the ball milling treatment is 1200-1500 r / min, and the time of the ball milling treatment is 18-25 min; the calcination temperature is increased to 900-1050° C. at a rate of 2-5° C. / min, and the calcination is performed for 1-3 h.

2. The method for preparing cobalt green pigment according to claim 1, characterized in that: In step (1), the cobalt source includes one or more of cobalt sulfate, cobalt chloride or cobalt nitrate and hydrates thereof; the zinc source includes one or more of zinc sulfate, zinc chloride or zinc nitrate and hydrates thereof; and the chromium source includes one or more of chromium trichloride, chromium sulfate or chromium nitrate and hydrates thereof.

3. The method for preparing cobalt green pigment according to claim 1, characterized in that: In step (1), the stirring and mixing temperature is room temperature, the stirring speed is 500-600 r / min, and the time is 30-60 min; the pH is adjusted to 8-10, and the pH value is adjusted with an alkaline solution with a concentration of 1-3 mol / L; the alkali is sodium hydroxide and / or potassium hydroxide.

4. The method for preparing cobalt green pigment according to claim 1, characterized in that: In step (3), the protective atmosphere is one or more of nitrogen, argon or helium.

Citation Information

Patent Citations

  • Preparation method for nano cobalt green pigment powder

    CN108726580A

  • Infrared reflection cobalt green pigment and preparation process thereof

    CN115353753A